Applying e-commerce marketing for global economic development in Medan. Issue 1 (April 2020) - Stella; Ginting, B; Saidin, O K; Azwar, T K D
Abstract: The information technology development has increased the trading throughout the world. The goods and services trading business use e-commerce to develop marketing strategies, including Medan. In 2018 the community who used the e-commerce in trading as much as 54, 68%, but in 2019 it had been increasing become 64, 8%. However, the influence of technological advances is increasingly widespread in a variety of potential challenges faced by both business, individuals and society. This present has been an appealing situation to discuss the concept of e-commerce, which can improve the economy. This research uses the prescriptive normative method. The data are legal rules and practices to occur in e-commerce trading of goods and services. This study shows the existence of the seller provide price higher than the market prices, the seller doesn't send the quality goods to the online buyers, and the seller doesn't confirm payments of the online buyers. It makes the negative impact on the consumer confidence to the seller, but also hampering the economic development of society. E-commerce sellers should apply the green marketing concept and conduct the legal marketing responsibility. The implementation of green marketing concept is beneficial not only for customer, but also for the regional development.